PENGARUH TINGKAT NAUNGAN DAN CEKAMAN AIR TERHADAP LAJU PERTUMBUHAN RELATIF TUMBUHAN Ageratum conyzoides Linn. - Riski Busaifi (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2016)
This research was done to determine the effect of shelter and drought stress Relative Growth Rate of plant Ageratum conyzoides Linn. The experiment was conducted at Madame Agricultural land in PPPPTK Pertanian Cianjur from December 2012 until February 2013. The experiment was using Split-plot Design with two factors. First is the degree of shelter as main plot which is consist of shelter 0%, 25%, 45% and 55%, as a drought subplot (% field capacity) consists of 100%, 80%, 60%, and 40% of field capacity (KL). There are 16 combinations of treatments with 3 repeat. Each unit treatment contained four plants which fully observed. The experimental results showed the level of shelter and water stress significantly on several variables observations. Shelter and water stress levels effect on long Relative Growth Rate plants week 4, Relative Growth Rate of leaf number 8th week, fresh weight, dry weight of plant Ageratum conyzoides Linn.